2017
DOI: 10.4314/sajas.v47i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of commercial soybean meal with raw, full-fat soybean meal supplemented with varying levels of protease in diets of broiler chickens

Abstract: A 3 * 3 factorial study was used to evaluate the feed intake (FI), body weight gain (BWG), and feed conversion ratio (FCR) of broilers fed on the test diets. The commercial soybean meal (SBM) was replaced by raw, full-fat soybean meal (RSBM) at 0, 10 or 20%, equivalent to 0, 30 and 60 g/kg of diet, respectively, and the microbial protease was also supplemented in diets at 0.1, 0.2 or 0.3 g/kg, equivalent to ~7500, 15000 and ~22500 PROT/kg of diet, respectively. Microbial phytase (1000 FYT/kg) was uniformly add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
6
14
1
3
Order By: Relevance
“…Similarly, in the feeding trial (0 -25 days), the FI and BWG of birds on the PC and NC diets, which were supplemented with combined enzymes, were greatly improved, compared with the same measurements on other diets. These results in general are in line with previous reports (Malathi & Devegowda, 2001;Srinath et al, 2012;Erdaw et al, 2017a;2018) that better response were found in in vitro and in vivo experiments when combined microbial enzymes were used rather than individual application. These results suggest synergistic and combined effects of the two enzymes on ANF.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, in the feeding trial (0 -25 days), the FI and BWG of birds on the PC and NC diets, which were supplemented with combined enzymes, were greatly improved, compared with the same measurements on other diets. These results in general are in line with previous reports (Malathi & Devegowda, 2001;Srinath et al, 2012;Erdaw et al, 2017a;2018) that better response were found in in vitro and in vivo experiments when combined microbial enzymes were used rather than individual application. These results suggest synergistic and combined effects of the two enzymes on ANF.…”
Section: Discussionsupporting
confidence: 93%
“…Not only were the combined microbial enzymes effective in the latter phase of this study, but supplementation of microbial protease alone into the NC diet contributed to approximately 5.3% and 22.5%, or 11.4% increase in FI, BWG and feed efficiency, respectively, compared with birds on NC between 26 and 31 days. These results in general agree with previous reports (Ao, 2011;Barletta, 2011;Erdaw et al, 2017a;2017b;2017c) that ANF, for example proteinaceous anti-nutrients and stored proteins, can be broken down by supplementing the diets or ingredients with microbial protease or phytase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although soybean is primarily grown for oil, the seed can also be fed to poultry with oil intact (full fat). However, raw, full‐fat soybean (RFSB) contains antinutritional factors (ANFs) that negatively influence the utilisation of nutrients in poultry (Erdaw, Perez‐Maldonado, Bhuiyan, & Iji, , ,b; Pettersson & Pontoppidan, ). The best‐characterised ANFs in raw soybean seed are protease inhibitors, lectins and phytate (Pettersson & Pontoppidan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both commercial SBM and supplemental dietary oil could partially be replaced by inclusion of full‐fat SBM, but meals prepared from RSBM could contain high concentrations of antinutritional factors (ANF), such as trypsin inhibitors (TI), lectin and phytic acid. The best characterized ANFs in soya beans are protease inhibitors, lectins and phytates (Erdaw, Bhuiyan, & Iji, ; Erdaw, Shubiao, Perez‐Maldonado, & Iji, ; Pettersson & Pontoppidan, ). Nitrogen retention by animals can be negatively affected by the activity of TI, which results in increased metabolic nitrogen excretion (Banaszkiewicz, ; Dourado, Pascoal, Sakomura, Costa, & Biagiot, ).…”
Section: Introductionmentioning
confidence: 99%